Assessment of validity and comparison of two Spanish versions of the Geriatric Depression Scale - Bugallo-Carrera, Cesar; Dosil-Díaz, Carlos; Pereiro, Arturo X.; Anido-Rifón, Luís; Pacheco-Lorenzo, Moisés; Fernández-Iglesias, Manuel J.; Gandoy-Crego, Manuel (Frontiers in Psychology, 2023)
Introduction. The Geriatric Depression Scale is an instrument used to identify depression in people of an older age. The original English version of this scale has been translated into Spanish (GDS-VE); two shorter versions of 5- (GDS-5) and 15-items (GDS-15) have been developed. Aim of the study. To assess the validity and compare the 5- and 15-item Spanish versions of the GDS among the Spanish population. Materials and Methods. Five hundred and seventy-three Galicia residents aged > 50 years participated in this study. The following instruments were applied: the 19-item Control, Autonomy, Self-Realization and Pleasure scale, the Subjective Memory Complaints Questionnaire, the Mini-Mental State Examination test, the GDS-5, and the GDS-15. Results. We found differences in total score between GDS-5 and GDS-15 regarding the variable sex. Internal reliability for GDS-5 and GDS-15 was .495 and .715, respectively. Sensitivity and specificity for GDS-5 - with a cut-off value of 1 - was .517 and .650, respectively; for GDS-15 - with a cut-off value of 3 points - sensitivity was .755 and specificity .668. GDS-5 has a ROC curve of .617 and GDS-15 of .764. Conclusions. GDS-15, and to a greater extent GDS-5, should be revised or even reformulated to improve their diagnostic usefulness.